Fernando Díaz Orueta, Carlos González Villar, Lilia Sintes y María Luisa Lourés. Desarrollo urbano y pobreza : La ciudad de Posadas. Alicante, Argentina, Universidad de Alicante, 2000 - Vite Pérez, Miguel Ángel (Estudios Demográficos y Urbanos, 2002)
Fernando Díaz Orueta, Carlos González Villar, Lilia Sintes y María Luisa Lourés, Desarrollo urbano y pobreza: La ciudad de Posadas, Alicante, Argentina, Universidad de Alicante, 2000.